Relationship Between sCD163 and mCD163 and Their Implication in the Detection and Typing of Leprosy - Farag AGA; El Askary SA; Fathy WM; Elbassal F; Azzam AA; Tayel NR; Abdul Karim SS; Shehata WA (Dove Medical Press, 2020)
Azza Gaber Antar Farag,1 Shymaa A El Askary,2 Waleed M Fathy,3 Fathia Elbassal,3 Ayman Ali Azzam,4 Nermin Reda Tayel,5 Samah Saad Abdul Karim,6 Wafaa Ahmed Shehata1 1Dermatology, Andrology & STDs Department, Faculty of Medicine, Menoufia University, Al Menoufia, Egypt; 2Medical Microbiology and Immunology Department, Faculty of Medicine, Menoufia University, Minufya, Egypt; 3Clinical Pathology Department, Faculty of Medicine, Menoufia University, Minufya, Egypt; 4Clinical Biochemistry Department, National Liver Institute, Menoufia University, Minufya, Egypt; 5Department of Molecular Diagnostics and Therapeutics, Genetic Engineering Biotechnology Research Institute, Sadat City, Egypt; 6Dermatology Department, Shebin ElKom Teaching Hospital, Minufya, EgyptCorrespondence: Azza Gaber Antar FaragDermatology, Andrology & STDs Department, Faculty of Medicine, Menouﬁa University, Shebin ElKom, Al Menoufia 32511, EgyptTel +20 109 778 7204Fax +20 2482 226 454Email azzagaber92@yahoo.comBackground: Leprosy is a chronic contagious disease caused by Mycobacterium lepraea. CD163 is a monocyte trans-membrane glycoprotein receptor (mCD163) that sheds from the cell surface and circulates as a soluble (serum) form (sCD163). Changes in the mCD163 and sCD163 levels could mirror the categorization of inflammatory procedure, demonstrating a possible use of CD163 as a diagnostic indicator of inflammation.Objective: To investigate the possible role of CD163 (sCD163 and mCD163) in leprosy pathogenesis and to assess whether CD163 is a helpful inflammatory marker of leprosy development and typing.Patients and Methods: This case control study included 70 leprosy patients and 30 healthy controls. Leprosy patients were classified according to the Madrid criteria (1953) into: tuberculoid leprosy (TT), border-line leprosy (BL), and lepromatous leprosy (LL). For all participants, complete blood count (CBC), serum CD163 using ELISA and monocytes positive for CD163 using flow cytometry were done.Results: Leprosy patients had significantly low WBCs and platelet counts (p< 0.001) and had significantly higher sCD163 (p=0.025) and mCD163 (p=0.042) that were highest in LL followed by BL, then TT patients (p< 0.001). There was a significant positive correlation between mCD163 and sCD163 levels in leprosy patients (r=0.896, p< 0.001). ROC analysis revealed a significant role of serum sCD163 and of mCD163 positive monocytes in the detection (p< 0.001) and typing of leprosy (p=0.002 and p< 0.001, respectively).Conclusion: Both sCD163 and mCD163 positive monocytes may have an active role in leprosy pathogenesis. They could be potential biomarkers for leprosy detection and typing.Keywords: CD163 positive monocytes, flow cytometry, leprosy, sCD163